Documentary REAL-ism: Catfish and This Is Not a Film - Friedlander, Jennifer (Cinémas, 2015)
This article explores two recent documentary films, one of which may not be a documentary, the other of which may not be a film. Although starkly different in their subject matter and political stakes, both Catfish (Ariel Schulman and Henry Joost, 2010) and This Is Not a Film (Jafar Panahi and Mojtaba Mirtahmasb, 2011) point to underappreciated dimensions of filmic realism, in particular its propensity to evoke what I will call Real-ism—i.e. hints of the Real that emerge precisely when the symbolic framework governing reality becomes imperiled. Drawing upon Jacques Lacan’s notion of the Real and Jacques Rancière’s concept of the “aesthetic regime,” I will suggest that elements of conventional filmic realism have the potential to produce a politically destabilizing Real-ism which, rather than involving the representation of reality in any recognizable form, calls forth that which is necessarily excluded/repressed from the symbolic framework.